Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Paschen, Linda; Baumeister, Jochen (Gait & Posture)

Alterations of postural control across the menstrual cycle – A systematic review - Pohle, Carina; Paschen, Linda; Baumeister, Jochen (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

AnnoPy – Ein digitales Tool zur Förderung von Textkompetenzen. - Rezat, Sara; Scholle, Oliver (Medien im Deutschunterricht)

Mit digitalen Tools Peer-Feedback zu Texten geben. - Rezat, Sara (Deutsch 5-10)

Frömmigkeit als Antwort auf Krisen und Katastrophen? Die Erweckungsbewegung im 19. Jahrhundert in Lippe und der Lippische Gemeinschaftsbund - Pinsch, Jan Christian (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Die schriftbildliche Gestaltung von lexikalisch übernommenen Markennamen. Ein explorativer Wahrnehmungstest zum graduellen Entrenchment von Markennamen als multimodale Konstruktionen - Dübbert, Alexander (Beiträge zur Namenforschung)
Dieser Beitrag untersucht, inwiefern sich die kognitive Verankerung von der schriftbildlichen Gestaltung lexikalisch übernommener Markennamen nachweisen lässt. Dazu werden die Ergebnisse eines tachistoskopischen Wahrnehmungstests ausgewertet, bei dem einer Testgruppe die Schriftbilder (Logos) der Markennamen 'FÜR', 'Landliebe', 'MONSTER', 'GUT & GÜNSTIG', 'kinder' und 'ja!' mehrmals für Sekundenbruchteile (0,01s, 0,02s, 0,1s und 1,0s) und teils mit substituiertem Schriftzug präsentiert wurden. Insgesamt deutet die explorative Untersuchung – mit graduellen Abweichungen – in die Richtung, dass die Wahrnehmung des Schriftbilds zum Erkennen des dazugehörigen Markennamens führt. Dies ermöglicht die Schlussfolgerung, dass sich die getesteten Markennamen als multimodale Konstruktionen mit konstitutiver Schriftbildlichkeit qualifizieren.

Cognitive Training Improves Joint Stiffness Regulation and Function in ACLR Patients Compared to Healthy Controls - An, Yong Woo; Kim, Kyung-Min; DiTrani Lobacz, Andrea; Baumeister, Jochen; Higginson, Jill S.; Rosen, Jeffrey; Swanik, Charles Buz (Healthcare)
As cognitive function is critical for muscle coordination, cognitive training may also improve neuromuscular control strategy and knee function following an anterior cruciate ligament reconstruction (ACLR). The purpose of this case-control study was to examine the effects of cognitive training on joint stiffness regulation in response to negative visual stimuli and knee function following ACLR. A total of 20 ACLR patients and 20 healthy controls received four weeks of online cognitive training. Executive function, joint stiffness in response to emotionally evocative visual stimuli (neutral, fearful, knee injury related), and knee function outcomes before and after the intervention were compared. Both groups improved executive function following the intervention (p = 0.005). The ACLR group had greater mid-range stiffness in response to fearful (p = 0.024) and injury-related pictures (p = 0.017) than neutral contents before the intervention, while no post-intervention stiffness differences were observed among picture types. The ACLR group showed better single-legged hop for distance after cognitive training (p = 0.047), while the healthy group demonstrated no improvement. Cognitive training enhanced executive function, which may reduce joint stiffness dysregulation in response to emotionally arousing images and improve knee function in ACLR patients, presumably by facilitating neural processing necessary for neuromuscular control.
Keywords: Health Information Management; Health Informatics; Health Policy; Leadership and Management

Christliche Ethik: Der Klimawandel. Interpretationen - Unterrichtsmodell - Garske, Volker; Bürger, Markus; Hellgermann, Andreas; Jendt, Sebastian

Kafka trifft Markus: Intertextuelle Erarbeitung einer Szene aus "Heilung des Bartimäus" (Mk 10,46-52) - Garske, Volker

"Halt dich an mir fest!" - Der Seewandel Jesu im Spiegel moderner Popmusik - Garske, Volker

Investigation of the influence of process parameters on productivity in the LPBF process for the material Inconel 718 - Bödger, Christian; Gnaase, Stefan; Lehnert, Dennis; Tröster, Thomas (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The nickel-based alloy Inconel 718, which is used in aerospace technology, poses a great challenge to conventional machining due to its high strain hardening and toughness. Here, the laser powder bed fusion process (LPBF) offers an alternative with potential savings if sufficiently high productivity can be achieved. Based on the parameter study carried out, starting from the SLM Solutions standard parameters for the manufacturing of components, exposure parameters could be developed to realize manufacturing with 120 μm and 150 μm layer thickness, with almost the same geometric accuracy. For this purpose, the process parameters of laser power, focus diameter, hatch distance and scan speed were varied. The negative defocusing of the laser showed a positive effect on the density of the parts, realizing densities ≥ 99.94 %, with high dimensional stability and good mechanical properties. Considering the reduced manufacturing time of up to 61 %, a significant increase in productivity was achieved.

Comparative Study of the Influence of Heat Treatment and Additive Manufacturing Process (LMD & L-PBF) on the Mechanical Properties of Specimens Manufactured from 1.2709 - Gnaase, Stefan; Niggemeyer, Dennis; Lehnert, Dennis; Bödger, Christian; Tröster, Thomas (Crystals)
(1) This work answers the question of whether and to what extent there is a significant difference in mechanical properties when different additive manufacturing processes are applied to the material 1.2709. The Laser-Powder-Bed-Fusion (L-PBF) and Laser-Metal-Deposition (LMD) processes are considered, as they differ fundamentally in the way a part is manufactured. (2) Known process parameters for low-porosity parts were used to fabricate tensile strength specimens. Half of the specimens were heat-treated, and all specimens were tested for mechanical properties in a quasi-static tensile test. In addition, the material hardness was determined. (3) It was found that, firstly, heat treatment resulted in a sharp increase in mechanical properties such as hardness, elastic modulus, yield strength and ultimate strength. In addition to the increase in these properties, the elongation at break also decreases significantly after heat treatment. The choice of process, on the other hand, does not give either process a clear advantage in terms of mechanical properties but shows that it is necessary to consider the essential mechanical properties for a desired application.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Influence of response complexity on response inhibition for the basketball pump fake - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 55th Autumn Meeting of Experimental Cognitive Psychology (HExKoP))

Response inhibition for the basketball pump fake - Wickemeyer, Carolin; Güldenpenning, Iris; Weigelt, Matthias (Human Performance – Assessment, Intervention & Analysen. Abstractband der 55. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Lehrerprofessionalisierung im digital gestützten NT-Sachunterrricht - Schüßler, Marie; Tenberge, Claudia; Auf der Landwehr , Katja Maria; Meschede , Nicola; Windt , Anna; Ronnebaum, Marie-Theres; Brückmann, Maja (Posterbeitag im Rahmen der 50. Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik (GDCP) vom 11.-14.September 2023 in Hamburg - Postersymposium Lehrkräfteprofessionalisierung in den MINT-Kompetenzzentren)

Lehrkräfteprofessionalisierung für digital gestützten naturwissenschaftlich-technischen Sachunterricht - ComeNet Sachunterricht - Schüßler, Marie; Tenberge, Claudia; Auf der Landwehr , Katja Maria; Meschede , Nicola; Windt , Anna; Ronnebaum, Marie-Theres; Brückmann, Maja (Posterbeitag im Rahmen der Projekttagung des Projektverbundes ComeMINT Netzwerk vom 14.-15.Dezember 2023 in Aachen)

Plate Heat Exchangers for Condensation Processes: Recent Developments and Future Perspectives - Arsenyeva, Olga; Kapustenko, Petro; Tovazhnyanskyy, Leonid (Book of abstracts of The 7th Sustainable Process Integration Laboratory (SPIL) Scientific Conference in Conjunction with Renewable Energy System for Residential Building Heating and Electricity Production (RESHeat) Workshop)

Mathematical Model of Energy Efficiency for the Intelligent Residential Heating Systems - Polyvianchuk, Andrii; Semenenko, Roman; Tur, Oleg; Arsenyeva, Olga (Abstracts of the 7th Sustainable Process Integration Laboratory (SPIL) Scientific Conference in Conjunction with Renewable Energy)

Grammatik in deutschen und niederländischen DaF-Lehrbüchern: Synergien für den Deutschunterricht - Blachut, Alisa; Topalović, Elvira; Uhrig, Sissy (Der Deutschunterricht)